Assessing community empowerment for an innovative epidemiologic approach - Melo, Pedro (2020)
Community empowerment can be a process, but also the result of nursing care. To analyze it as a result there is an instrument that allows to quantify its level in nine domains. According to Melo (2020), health centers can be considered communities, becoming the potential target of community and public health nurses care, especially in the public health unit. One of the main functions of a public health unit is the epidemiological surveillance of the population’s health state. However, traditional epidemiological surveillance is focused on diseases and Melo (2020) proposes a new approach for epidemiology focused on people in what concerns nursing diagnosis. The aim of this research is to identify the level of empowerment of four Portuguese primary healthcare structures, named as ACeS, so as to improve the epidemiological surveillance of nursing diagnoses. As methodology, we developed four focus group with all nursing leaders from all primary care units of the four ACeS, using the Portuguese version of the empowerment assessment rating scale. The results present the level of community empowerment of each ACeS according to the nine domains of the scale. The needs of intervention to improve the ACeS empowerment were also identified in order to develop the epidemiological surveillance of nursing